Power and responsibility: re-presenting the Bible for children in the secular West - James, Rob (2025)
This article explores the challenges of translating the Bible for children within a secular Western context. It examines debates on selective adaptation, paraphrasing, and the inevitable interpretive biases that arise in children’s Bible translations. It highlights the tensions between textual fidelity and cultural sensitivity and a range of other concerns. Ultimately, it advocates a storytelling approach that includes interaction between teller and audience, so that the stories are co-created. At the same time, it suggests that transparency about where the original story can be located in a Bible is essential in a world of low biblical literacy.
Keywords: Translation; Storytelling; Paraphrase; children’s Bible